ANEMIA PADA POST PARTUM - Afria, Rahmi; Harni Susilawati, Enung; Fauzia, Fauzia (Politeknik Kesehatan Kemenkes Bandung, 2024)
Anemia is a complication that is postpartum mothers. The main cause is bleeding during the birth process. In 2023, 92 (8.47%) of the 1085 mothers who gave birth spontaneously will handle post-partum hemorrhage at the Sekarwangi Hospital. The aim of this midwifery care is to apply Post Partum Midwifery Care to Mrs. W aged 30 years P3A1 with moderate anemia at Sekarwangi Hospital.The method in preparing this assignment report is a case study. The form of documentation is SOAP. Data collection techniques obtained through interviews, physical and laboratory examination observations, the mother gave birth to her fourth child 8 hours ago, the mother had a miscarriage once, the mother complained of feeling weak, dizzy, her eyes were dizzy. Examination of vital signs showed blood pressure 90/60 mmHg, pulse 92x/m, respiration 21x/m, temperature 36.5 C, face, conjunctiva and gums pale, genital examination found blood output 50cc, and supporting examination with hemoglobin examination with results of 7.7 gr/dl. The analysis that can be confirmed is